Das interkulturelle Potenzial von Karikaturen im DaF-Unterricht - Utri, Reinhold (Glottodidactica, 2013)
Pictures/caricatures – as a part of culture are characteristic for a society (nation). In the process where different cultures get in touch pictures may play a role in teaching a foreign language. Introduction into an intercultural topic, intensive discussion – there are many possibilities for a teacher to show his/her students the life in a German-speaking country in its various facets. Caricatures can combine politics, society, religion, culture and sense of humour with an enrichment of the language used in classroom – at the same time supporting the development of the intercultural competence of the students.